PENINGKATAN KEMAMPUAN MEMBACA MELALUI MODEL PEMBELAJARAN NGAKAK - Dava Agil Pamungkas; Adi Winanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the researcher's observations regarding students' low reading proficiency. The research focuses on efforts to improve students' reading skills through the implementation of the NGAKAK (Set your storytelling intention – Mine for unique ideas – Structure the plot – Develop your expression – Perform the story – Share comments) learning model. The general objective of the study is to examine the implementation of the NGAKAK learning model in enhancing students' reading skills and to assess the improvement in these skills following the model's application. The study employs the Classroom Action Research method, adapting the Kemmis and Taggart model, and was conducted over two cycles. The subjects of the study consisted of 20 students. Data collection was carried out through tests, analysis of learning observation results, and field notes. The results from tests administered in each cycle, combined with observation findings and field notes, indicate positive progress in learning through the implementation of the NGAKAK learning model.